Stabilisation of SrAl2O4 hexagonal phase at RT in ZnO-SrAl2O4 nanocomposite - Singh V.P.; Rai S.B.; Mishra H.; Rath C. (My University, 2025)
In this article, we have reported hexagonal phase of SrAl2O 4 (SAO) at room temperature by synthesizing ZnO-SAO nanocomposite which has been found to be difficult to achieve. Through combustion technique, we have made ZnO(20%)-SAO(80%) nanocomposite and revealed a good dispersion of ZnO in SAO matrix. A stable hexagonal phase at RT has been obtained in the composite sample calcined at 700 and 800 °C. Further, increasing the calcination temperature to 1000 and 1200°C, hexagonal phase transforms to monoclinic. From photoluminescence studies, we have observed an emission close to white light with changing the calcination temperature. © 2013 American Institute of Physics.